Draft genome sequence of Flavobacterium sp. strain PL002, isolated from Antarctic Porphyra algae - Teoh, Chui Peng; Paris, Lavin; Nazalan Najimudin; Lee, Ping Chin; Iancu, Lavinia; Purcarea, Cristina; Wong, Clemente Michael Vui Ling (American Society for Microbiology, 2021)
Here, we report the draft genome sequence of Flavobacterium sp. strain PL002, isolated from Antarctic Porphyra algae. The 4,299,965-bp genome sequence is assembled into 170 contigs, has 32.92% GC content, and 3,734 predicted genes.